Thigh muscle fat fraction is independently associated with impaired glucose metabolism in individuals with obesity - Xiaobing Lu; Jiang Yue; Qianjing Liu; Shengyun He; Ying Dong; Ming Zhang; Yicheng Qi; Minglan Yang; Wang Zhang; Hua Xu; Qing Lu; Jing Ma (Endocrine Connections, 2023)
Background: The aim of this study was to address the intramuscular adipose tissue (IMAT) accumulation in the lower extremities and further detect the relationship between adipose tissue (AT) distribution in the muscle and glucose metabolism in subjects with obesity. Methods: We conducted a cross-sectional study in 120 Chinese obese adults (80 male and 40 female) with BMI ≥ 28 kg/m2. MRI was applied to access the IMAT content in lower extremities. The oral glucose tolerance test was used to evaluate the glucose metabolism and insulin secretion in all individuals. The correlations between glucose metabolism and the fat content of the lower extremities were further assessed. Results: Among 120 included subjects, 54 were classified as subjects with normal glucose tolerance (NGT) and 66 with impaired glucose regulation (IGR). We presented that those with IGR had higher fat accumulation in semitendinosus, adductor magnus, gracilis and sartorius than those with NGT (all P < 0.05). In sex-specific analyses, females have higher IMAT in adductor magnus than males (P < 0.001). Males with IGR had higher fat fraction of semitendinosus and sartorius than those with NGT (P = 0.020, P = 0.014, respectively). Logistic regression analyses revealed that IMAT content in semitendinosus was the independent factor of IGR in individuals with obesity after adjustment for age, gender, triglycerides, creatinine and albumin (odds ratio: 1.13, 95% CI: 1.02–1.26, P = 0.024). Conclusions: Increased adipose tissue accumulation in thigh muscles was associated with glucose dysregulation in patients with obesity. IMAT content in semitendinosus may serve as a possible risk factor for impaired glucose metabolism.